Optical laminate, polarizing plate, surface sheet, panel and image display device using the optical laminate, and manufacturing method and selection method of optical laminate
Patent Information
- Application Number
- CN202580024974.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-02-27
- Filing Date
- 2025-04-01
- Publication Date
- 2026-11-03
AI Technical Summary
Existing anti-glare films suffer from reduced adhesion and scratch resistance between the substrate and the anti-glare layer over time, leading to a decline in the performance of the optical laminate.
By controlling the concentration of propyl acetate in the optical laminate to be above 0.02 mg/m2 and below 15.00 mg/m2, and using propyl acetate as a solvent for the functional layer coating liquid, at least one functional layer, preferably including an anti-glare layer, is formed on the substrate to improve adhesion and scratch resistance.
It effectively inhibits the decrease in adhesion and scratch resistance over time, and improves the performance stability and durability of optical laminates.
Smart Images

Figure CN123036531A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to optical laminates, polarizers, surface plates, panels and image display devices using said optical laminates, as well as methods for manufacturing optical laminates and methods for selecting optical laminates. Background Technology
[0002] Optical layers are sometimes incorporated into image display devices such as televisions, laptop PCs, and desktop PC monitors. For example, optical layers are sometimes placed on the surface of the image display device to suppress the reflection of lighting and background elements such as people, or to suppress surface reflection.
[0003] As an optical laminate, anti-glare films have been proposed, for example, in Patent Documents 1-3.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Publication No. 2023-516178
[0007] Patent Document 2: Japanese Patent Application Publication No. 2021-124616
[0008] Patent Document 3: Japanese Patent Application Publication No. 2022-183161 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] The anti-glare films in Patent Documents 1-3 have an anti-glare layer on the substrate, which enables good anti-glare performance. However, with the passage of time, conventional anti-glare films like those in Patent Documents 1-3 frequently experience a decrease in the adhesion between the substrate and the anti-glare layer, as well as a decrease in scratch resistance.
[0011] The present disclosure addresses the following: providing an optical laminate capable of suppressing the degradation of adhesion and scratch resistance over time. The present disclosure also addresses the following: providing polarizers, surface plates, panels, and image display devices capable of suppressing the degradation of adhesion and scratch resistance over time. Furthermore, the present disclosure addresses the following: providing a method for efficiently manufacturing an optical laminate capable of suppressing the degradation of adhesion and scratch resistance over time. Finally, the present disclosure addresses the following: providing a method for efficiently selecting an optical laminate capable of suppressing the degradation of adhesion and scratch resistance over time.
[0012] Methods for solving problems
[0013] This disclosure provides the following <1> ~ <7> .
[0014] <1> An optical laminate having at least one or more functional layers on a substrate, wherein a concentration of propyl acetate in the optical laminate obtained by quantitative analysis using gas chromatography is 0.02 mg / m 2 or less and 15.00 mg / m 2 or more.
[0015] <2> A polarizing plate having a polarizing element, a first transparent protective plate disposed on one side of the polarizing element, and a second transparent protective plate disposed on the other side of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical laminate of <1>.
[0016] <3> A surface plate for an image display device, which is a surface plate for an image display device having a protective film attached to a resin plate or a glass plate, wherein the protective film is the optical laminate of <1>.
[0017] <4> A panel having a display element and an optical laminate disposed on the light exit surface side of the display element, wherein the optical laminate of <1> is included as the optical laminate.
[0018] <5> An image display device including the panel of <4>.
[0019] <6> A method for manufacturing an optical laminate, which includes a step of applying a functional layer coating liquid on a substrate, and a step of drying the functional layer coating liquid, wherein the functional layer coating liquid contains propyl acetate as a solvent, and a concentration of propyl acetate in the optical laminate obtained by quantitative analysis using gas chromatography is 0.02 mg / m 2 or less and 15.00 mg / m 2 or more.
[0020] <7> A selection method of an optical laminate, which selects an optical laminate satisfying the following selection condition, Selection condition of the optical laminate: An optical laminate having at least one or more functional layers on a substrate, wherein a concentration of propyl acetate in the optical laminate obtained by quantitative analysis using gas chromatography is 0.02 mg / m 2 or less and 15.00 mg / m 2 or more.
[0021] Effects of the Invention
[0022] The optical laminate, polarizing plate, surface plate, panel, and image display device of the present disclosure can suppress temporal decrease in adhesiveness and scratch resistance. The manufacturing method of the optical laminate of the present disclosure can efficiently select an optical laminate that can suppress temporal decrease in adhesiveness and scratch resistance. The selection method of the optical laminate of the present disclosure can efficiently select an optical laminate that can suppress temporal decrease in adhesiveness and scratch resistance. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 is a schematic cross-sectional view showing an embodiment of the optical laminate of the present disclosure.
[0024] Figure 2 is a cross-sectional view showing an embodiment of the panel of the present disclosure. DETAILED DESCRIPTION
[0025] Hereinafter, an embodiment of the present disclosure will be described.
[0026] [Optical laminate]
[0027] The optical laminate of the present disclosure is as follows.
[0028] An optical laminate having at least one or more functional layers on a substrate, wherein With respect to the concentration of propyl acetate in the optical laminate obtained by quantitative analysis using gas chromatography, the concentration of propyl acetate is 0.02 mg / m 2 or more and 15.00 mg / m 2 or more.
[0029] Figure 1 is a schematic cross-sectional view of the cross-sectional shape of the optical laminate 100 of the present disclosure.
[0030] Figure 1 The optical laminate 100 of has a functional layer 20 on a substrate 10.The optical laminate 100 of has a first functional layer 21 and a second functional layer 22 as the functional layer 20. As the first functional layer 21, for example, an anti-glare layer can be cited. As the second functional layer 22, for example, a low refractive index layer can be cited. Figure 1
[0031] Figure 1 is a schematic cross-sectional view. That is, the scale of each layer constituting the optical laminate 100 is patterned for easy illustration, and is different from the actual scale. Figure 2 The same also applies.
[0032] The optical laminate of the present disclosure is not limited to Figure 1The optical laminate of the present disclosure can have only one layer as the functional layer, or can have three or more layers as the functional layer. In addition, the optical laminate of the present disclosure can have the functional layer on both sides of the substrate.
[0033] <Substrate>
[0034] As the substrate, it is preferable to have light transmittance, smoothness, and heat resistance, and excellent mechanical strength. As such a substrate, plastic films such as polyester, triacetyl cellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyether sulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate, polyurethane, and cyclo-olefin polymer (COP) can be given. The substrate can be a plastic film obtained by laminating two or more plastic films.
[0035] Among the plastic films, a polyester film subjected to stretching processing is preferable in terms of mechanical strength and dimensional stability, and a biaxially stretched polyester film is more preferable. As the polyester film, a polyethylene terephthalate film, a polyethylene naphthalate film, and the like can be given.
[0036] Among the plastic films, a TAC film (triacetyl cellulose film) and an acrylic film are preferable because they easily provide good light transmittance and optical isotropy. The TAC film and the acrylic film are also suitable in that they easily form a permeation layer described later, and thus easily provide good adhesion of the optical laminate.
[0037] Among the plastic films, a COP film and a polyester film are preferable because they have excellent weather resistance.
[0038] A plastic film having an easy-adhesion layer is also preferable. If propyl acetate permeates into the easy-adhesion layer, the affinity of the easy-adhesion layer to the functional layer increases, and thus the adhesion of the easy-adhesion layer to the functional layer easily increases. Therefore, a plastic film having an easy-adhesion layer is suitable in that it easily provides good adhesion of the optical laminate. As the plastic film having an easy-adhesion layer, a polyester film having an easy-adhesion layer is preferable, and a polyethylene terephthalate film having an easy-adhesion layer is more preferable.
[0039] As the raw material of the plastic film, one or more selected from the group consisting of "newly synthesized raw materials", "recycled raw materials", and "biomass-derived raw materials" can be given. In order to reduce the load on the environment, it is preferable that the raw material of the plastic film contain a biomass-derived raw material. The biomass-derived raw material refers to a raw material derived from a plant.
[0040] Whether or not the raw material is a biomass-derived raw material can be determined by measuring the radioactivity of carbon (C). It is known that carbon dioxide in the atmosphere contains a certain proportion (105.5 pMC) of carbon (C) derived from plants. 14 It is known that carbon dioxide in the atmosphere contains a certain proportion (105.5 pMC) of carbon (C) derived from plants.14 C, therefore, in plants that grow by absorbing carbon dioxide from the atmosphere 14 The carbon content is also around 105.5 pMC. Furthermore, it is known that fossil fuels contain almost no carbon. 14 C. Therefore, by determining the carbon atoms contained in all the carbon atoms in the raw material... 14 The proportion of C can determine whether the raw material is derived from biomass.
[0041] To ensure good mechanical strength and dimensional stability, and to reduce environmental impact, the substrate is preferably a polyester film containing polyester derived from biomass.
[0042] As described below, the optical laminate of this disclosure contains propyl acetate as a solvent for the functional layer coating liquid. Because propyl acetate evaporates quickly, the desired optical properties can be obtained even at lower drying temperatures. That is, in the optical laminate of this disclosure, the desired optical properties can be easily obtained even when using a plastic film with a low heat resistance temperature. Therefore, the optical laminate of this disclosure increases the options for substrates. Examples of plastic films with low heat resistance temperatures include TAC films and acrylic films.
[0043] In this specification, propyl acetate refers to at least one of n-propyl acetate and isopropyl acetate.
[0044] The thickness of the substrate is preferably 5.0 μm or more and 300.0 μm or less, more preferably 20.0 μm or more and 200.0 μm or less, and even more preferably 30.0 μm or more and 120.0 μm or less.
[0045] When it is desired to thin the optical laminate, the preferred upper limit for the thickness of the substrate is 100 μm or less, and more preferably 80.0 μm or less. Furthermore, when the substrate is a low-moisture-permeability substrate such as polyester, COP, or acrylic, the preferred upper limit for the thickness of the substrate used for thinning is 60.0 μm or less, and more preferably 40.0 μm or less. Even in the case of large-screen displays, if the upper limit for the substrate thickness is within the above range, it is also preferable in terms of minimizing strain.
[0046] In this specification, the thickness of the substrate is measured using a general-purpose film thickness gauge. The substrate thickness is determined by averaging the values at any 10 points as described above. A digital standard external micrometer (Mitutoyo, model "MD C-25SX") can be used as an example of a film thickness gauge.
[0047] Unless otherwise specified, all measurements in this manual, such as layer thickness, are performed at a temperature of 23±1℃ and a relative humidity of 40% to 65%.
[0048] The substrate preferably has a permeable layer on the side containing the functional layer. The permeable layer facilitates good adhesion between the substrate and the functional layer. This good adhesion also improves the scratch resistance of the optical laminate. Furthermore, the permeable layer helps suppress the generation of interference fringes when stacking multiple optical laminates or when stacking optical laminates with other light-transmitting components. The permeable layer is preferably a permeable layer containing propyl acetate.
[0049] If the penetration layer is too thick, a large amount of substrate components or functional layer components will flow into the functional layer side or the substrate side, which can reduce the scratch resistance of the optical laminate. Examples of substrate components include resins, plasticizers, and UV absorbers. Plasticizers and UV absorbers tend to reduce the scratch resistance of optical laminates.
[0050] Furthermore, due to the significant influx of functional layer components into the substrate side, the physical properties of the optical laminate sometimes change excessively. When the functional layer contains particles and binder resin, if a large amount of binder resin flows into the substrate side, the amount of resin binding the particles decreases, making the particles easier to scrape off, thus tending to reduce the scratch resistance of the optical laminate. Additionally, if a large amount of binder resin flows into the substrate side, the particles become excessively exposed on the surface of the functional layer, thus tending to cause whitening of the optical laminate and a significant change in appearance.
[0051] When the thickness of the permeation layer is too thin, it is sometimes difficult to achieve good adhesion between the substrate and the functional layer.
[0052] Therefore, the thickness of the permeation layer is preferably 0.20 μm or more and 1.50 μm or less, more preferably 0.30 μm or more and 1.00 μm or less, and even more preferably 0.53 μm or more and 0.70 μm or less.
[0053] In the technical features shown in this specification, when options for upper and lower limits of multiple numerical values are shown respectively, embodiments are described that combine a range of options selected from the upper limit and options selected from the lower limit. For example, embodiments of the thickness range of the aforementioned permeation layer include 0.20 μm to 1.50 μm, 0.20 μm to 1.00 μm, 0.20 μm to 0.70 μm, 0.30 μm to 1.50 μm, 0.30 μm to 1.00 μm, 0.30 μm to 0.70 μm, 0.53 μm to 1.50 μm, 0.53 μm to 1.00 μm, and 0.53 μm to 0.70 μm.
[0054] The ratio of the thickness of the permeation layer to the thickness of the substrate is preferably 0.001 or more and 0.500 or less, more preferably 0.003 or more and 0.350 or less, and even more preferably 0.005 or more and 0.200 or less.
[0055] By setting the ratio to 0.001 or higher, good adhesion between the substrate and the functional layer can be easily achieved. By setting the ratio to 0.500 or lower, the reduction in the strength of the substrate can be suppressed, and the reduction in the scratch resistance of the optical laminate can be easily suppressed.
[0056] The thickness of the permeation layer was measured using a sample with a cross-section exposed by STEM (scanning transmission electron microscopy). Any location from 20 STEM-based cross-sectional photographs of the sample was selected, and the average value of these 20 locations was taken as the thickness of the permeation layer of the optical laminate of this disclosure.
[0057] The sample can be prepared, for example, by the steps (A1) to (A2) below. In cases where the penetration layer is difficult to identify due to insufficient contrast, the sample can be stained with dyes such as osmium tetroxide, ruthenium tetroxide, or phosphotungstic acid.
[0058] (A1) After cutting the optical laminate into samples of arbitrary size, an embedded sample is prepared by embedding the cut sample in resin. The cut sample is a strip with a length of 10 mm and a width of 3 mm. The resin used for embedding is epoxy resin.
[0059] The embedded sample is obtained as follows: after placing the cut sample inside a silicon embedding plate, embedding resin flows in, and after the embedding resin solidifies, the cut sample and the embedding resin encapsulating it are removed from the silicon embedding plate. The embedded sample is in block shape.
[0060] (A2) Cut the block-shaped embedded sample with a diamond knife to make a slice sample.
[0061] As described above, uniform slices with a thickness of 60 nm or more and 100 nm or less, obtained from cutting the block-shaped embedded sample, without defects such as pores, are used as samples for measurement.
[0062] The total light transmittance of the substrate according to JIS K7361-1:1997 is preferably 70% or more, more preferably 80% or more, and even more preferably 85% or more.
[0063] The haze of the substrate according to JIS K7136:2000 is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less.
[0064] To improve adhesion, the surface of the substrate can be subjected to physical treatments such as corona discharge treatment, or chemical treatments. Additionally, the substrate can have an easy-to-adhere layer on its surface.
[0065] <Functional Layer>
[0066] The optical laminate disclosed herein has at least one functional layer on a substrate.
[0067] The optical laminate of this disclosure preferably includes one or more layers selected from a hard coating layer, an anti-glare layer, an anti-reflective layer, an anti-fouling layer, an antistatic layer, and a conductive layer as functional layers. More preferably, the optical laminate of this disclosure includes an anti-glare layer as a functional layer.
[0068] The following (1) to (18) are embodiments of the optical laminate structure of the present disclosure. In the following (1) to (18), " / " indicates the interface of the layer.
[0069] (1) Substrate / hard coating
[0070] (2) Substrate / Anti-glare layer
[0071] (3) Substrate / Hard coating / Anti-reflective layer
[0072] (4) Substrate / Anti-glare layer / Anti-reflection layer
[0073] (5) Substrate / Hard coating / Antifouling layer
[0074] (6) Substrate / Anti-glare layer / Anti-fouling layer
[0075] (7) Conductive layer / substrate / hard coating
[0076] (8) Conductive layer / substrate / anti-glare layer
[0077] (9) Antistatic layer / substrate / hard coating
[0078] (10) Antistatic layer / substrate / anti-glare layer
[0079] (11) Conductive layer / substrate / hard coating / anti-reflective layer
[0080] (12) Conductive layer / substrate / anti-glare layer / anti-reflection layer
[0081] (13) Antistatic layer / substrate / hard coating / antireflective layer
[0082] (14) Antistatic layer / substrate / anti-glare layer / anti-reflection layer
[0083] (15) Conductive layer / substrate / hard coating / anti-fouling layer
[0084] (16) Conductive layer / substrate / anti-glare layer / anti-fouling layer
[0085] (17) Antistatic layer / substrate / hard coating / antifouling layer
[0086] (18) Antistatic layer / substrate / anti-glare layer / anti-fouling layer
[0087] The total thickness of the functional layers is preferably 20.0 μm or less, more preferably 15.0 μm or less, and even more preferably 10.0 μm or less. By making the total thickness of the functional layers 20.0 μm or less, the total concentration of propyl acetate in the optical laminate can be easily made to be 15.00 mg / m³. 2 the following.
[0088] If the total thickness of the functional layers is too thin, it will be difficult to impart scratch resistance to the optical laminate. Therefore, the total thickness of the functional layers is preferably 2.0 μm or more, more preferably 4.0 μm or more, and even more preferably 6.0 μm or more.
[0089] In this specification, the thickness of the functional layer is measured using a sample with an exposed cross-section of the optical laminate by STEM (scanning transmission electron microscopy). Any portion of the STEM-based cross-sectional photographs of 20 of the samples is selected, and the average value of these 20 portions is taken as the thickness of the functional layer of the optical laminate of this disclosure.
[0090] Functional layers may include adhesive components and additives.
[0091] The binder component is preferably resin. That is, the binder component is preferably binder resin.
[0092] To facilitate good scratch resistance, the adhesive resin preferably comprises a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, and more preferably a cured product comprising an ionizing radiation curable resin composition.
[0093] The adhesive resin may include a thermoplastic resin to the extent that it does not impair the effects of this disclosure.
[0094] In order to facilitate good scratch resistance, the ratio of the cured product of the curable resin composition to the total amount of the adhesive resin is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.
[0095] A thermosetting resin composition is a composition that contains at least a thermosetting resin and is a resin composition that is cured by heating.
[0096] Examples of thermosetting resins include acrylic resins, polyurethane resins, phenolic resins, urea-melamine resins, epoxy resins, unsaturated polyester resins, and silicone resins. In thermosetting resin compositions, curing agents are added to these curing resins as needed.
[0097] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter also referred to as "ionizing radiation curable compound"). Examples of ionizing radiation curable functional groups include olefinic unsaturated groups such as (meth)acryloyl, vinyl, and allyl, as well as epoxy and oxetyl groups. As the ionizing radiation curable compound, compounds having olefinic unsaturated groups are preferred, compounds having two or more olefinic unsaturated groups are more preferred, and polyfunctional (meth)acrylate compounds having two or more olefinic unsaturated groups are even more preferred. Both monomers and oligomers can be used as polyfunctional (meth)acrylate compounds.
[0098] Ionizing radiation refers to ionizing rays in electromagnetic waves or charged particle beams that contain energy quanta capable of polymerizing or cross-linking molecules. Ultraviolet (UV) or electron (EB) beams are commonly used. In addition, electromagnetic waves such as X-rays and gamma rays, as well as charged particle beams such as alpha rays and ionizing rays can also be used.
[0099] Among polyfunctional (meth)acrylate compounds, examples of difunctional (meth)acrylate monomers include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxydiacrylate, bisphenol A tetrapropoxydiacrylate, and 1,6-hexanediol diacrylate.
[0100] Examples of (meth)acrylate monomers with three or more functions include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid modified tri(meth)acrylate.
[0101] The aforementioned (meth)acrylate monomers can modify a portion of the molecular backbone. For example, the aforementioned (meth)acrylate monomers can also be monomers modified by using ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl groups, cyclic alkyl groups, aromatic groups, bisphenols, etc., to modify a portion of the molecular backbone.
[0102] Examples of polyfunctional (meth)acrylate oligomers include urethane (meth)acrylates, epoxy (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, and other acrylate polymers.
[0103] Carbamate (meth)acrylates are obtained, for example, by reacting polyols and organic diisocyanates with hydroxy (meth)acrylates.
[0104] Preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc., with (meth)acrylate; (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc., with polybasic acids and (meth)acrylate; and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc., with phenols and (meth)acrylate.
[0105] The weight-average molecular weight of the polyfunctional (meth)acrylate oligomer is preferably 500 or more and 3000 or less, more preferably 700 or more and 2500 or less.
[0106] In this specification, the weight-average molecular weight is the average molecular weight determined by GPC analysis and converted to standard polystyrene.
[0107] Furthermore, for purposes such as adjusting the viscosity of the functional layer coating solution, monofunctional (meth)acrylates can be used as ionizing radiation curing compounds. Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate.
[0108] The aforementioned ionizing radiation curing compounds can be used alone or in combination of two or more.
[0109] When the ionizing radiation curing compound is an ultraviolet curing compound, the ionizing radiation curing resin composition preferably contains additives such as photopolymerization initiators and photopolymerization accelerators.
[0110] As photopolymerization initiators, one or more can be selected from acetophenone, benzophenone, α-hydroxyalkyl phenyl ketone, Mischel ketone, benzoin, benzyl dimethyl ketal, benzoylbenzoate, α-acyl oxime ester, thioxanone, etc.
[0111] Photopolymerization accelerators can reduce polymerization hindrance caused by air during curing and accelerate the curing speed. Examples of accelerators include isoamyl p-dimethylaminobenzoate and ethyl p-dimethylaminobenzoate.
[0112] When the adhesive resin contains a cured product of an ionizing radiation curable resin composition, the ionizing radiation curable resin composition may contain polyfunctional (meth)acrylate oligomers in addition to polyfunctional (meth)acrylate monomers.
[0113] The mass ratio of polyfunctional (meth)acrylate monomer to polyfunctional (meth)acrylate oligomer (mass of polyfunctional (meth)acrylate monomer: mass of polyfunctional (meth)acrylate oligomer) is preferably 5:95 to 60:40, more preferably 20:80 to 60:40, and even more preferably 40:60 to 60:40.
[0114] Multifunctional (meth)acrylate monomers readily increase the crosslinking density of the coating, resulting in good scratch resistance. However, compared to multifunctional (meth)acrylate oligomers, multifunctional (meth)acrylate monomers penetrate the substrate more easily; therefore, excessive addition can sometimes lead to an overly thick penetration layer. Thus, by using multifunctional (meth)acrylate monomers and multifunctional (meth)acrylate oligomers in the aforementioned mass ratio, it is easy to achieve good scratch resistance in the optical laminate.
[0115] As described above, the functional layer preferably contains additives in addition to the adhesive components.
[0116] The additive can be selected from common materials based on the function of the functional layer. When the functional layer is an anti-glare layer, it is preferable to include particulate matter as an additive. When the functional layer is an anti-reflective layer, it is preferable to include high-refractive-index or low-refractive-index particles as an additive. The anti-reflective layer can be a single layer or multiple layers of a low-refractive-index layer. For example, a two-layer anti-reflective layer with a high-refractive-index layer and a low-refractive-index layer can be used. When the functional layer is an anti-fouling layer, it is preferable to include an anti-fouling agent as an additive. When the functional layer is an antistatic layer, it is preferable to include an antistatic agent as an additive. When the functional layer is a conductive layer, it is preferable to include a conductive agent as an additive.
[0117] Functional layers such as anti-glare layers may contain particles. Examples of particles include one or more types selected from organic and inorganic particles.
[0118] Examples of inorganic particles include silicon dioxide, alumina, zirconium oxide, and titanium oxide, with silicon dioxide being preferred. Among inorganic particles, amorphous inorganic particles are preferred, and amorphous silicon dioxide is more preferred.
[0119] Examples of organic particles include particles containing one or more resins selected from polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, organosilicon, fluorinated resin and polyester resin.
[0120] The average particle size is preferably 1.0 μm or more and 5.5 μm or less, more preferably 1.3 μm or more and 5.0 μm or less, and even more preferably 1.5 μm or more and 4.5 μm or less.
[0121] In this specification, the average particle size refers to the value obtained as the volume average value d50 in laser diffraction.
[0122] Regarding the content of particles, relative to 100 parts by weight of the binder component, the lower limit is preferably 0.5 parts by weight or more, more preferably 1.0 parts by weight or more, even more preferably 2.0 parts by weight or more, and the upper limit is preferably 30.0 parts by weight or less, more preferably 25.0 parts by weight or less, even more preferably 20.0 parts by weight or less.
[0123] Functional layers such as low-refractive-index layers can contain low-refractive-index particles. Examples of low-refractive-index particles include hollow particles and solid particles.
[0124] The hollow and solid particles can be made of any inorganic or organic compound, such as silicon dioxide or magnesium fluoride, but silicon dioxide is preferred for its low refractive index and strength. That is, the low refractive index layer preferably contains hollow silicon dioxide particles. Furthermore, in addition to hollow silicon dioxide particles, the low refractive index layer preferably further contains solid silicon dioxide particles.
[0125] The average primary particle size of hollow particles is preferably smaller than the thickness of the low-refractive-index layer, for example, 1 nm or more and 150 nm or less. The average primary particle size of solid particles is preferably smaller than the thickness of the low-refractive-index layer, for example, 0.5 nm or more and 100 nm or less.
[0126] The average primary particle size of low-refractive-index particles and high-refractive-index particles (described later) can be calculated by the following operations (B1) to (B3).
[0127] (B1) Use TEM or STEM to photograph the cross-section of the optical laminate. Set the accelerating voltage of TEM or STEM to 10kV to 30kV and the magnification to 50,000 to 300,000 times.
[0128] (B2) Extract any 10 particles from the observed image and calculate the particle size of each particle. The particle size is set such that the distance between the two parallel straight lines is the maximum when the cross-section of each particle is clamped by any two parallel straight lines.
[0129] (B3) Perform the same operation 5 times in another image of the same sample, and take the average value of the total 50 particle sizes as the average first particle size.
[0130] Examples of high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide.
[0131] The average primary particle size of the high refractive index particles is preferably smaller than the thickness of the high refractive index layer, for example, greater than 2 nm and less than 200 nm.
[0132] -Formation of Functional Layers-
[0133] A functional layer can be formed, for example, by applying a functional layer coating liquid containing the components constituting the functional layer and a solvent to a substrate. After applying the functional layer coating liquid to the substrate, a drying process can be performed as needed.
[0134] Coating methods include gravure coating, bar coating, die coating, and roller coating.
[0135] Solvents can be exemplified by, for example, ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated hydrocarbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (isopropanol, butanol, cyclohexanol, etc.), cellosols (methyl cellosol, ethyl cellosol, etc.), glycol ethers (propylene glycol monomethyl ether acetate, etc.), acetic acid cellosols, sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc., or mixtures of these.
[0136] The optical laminates disclosed herein use at least propyl acetate as a solvent for the functional layer coating solution. In this specification, propyl acetate refers to at least one of n-propyl acetate and isopropyl acetate.
[0137] Because propyl acetate evaporates rapidly, the desired optical properties can be obtained even at lower drying temperatures. Therefore, using propyl acetate as a solvent is preferred in terms of increasing the selection of substrates. Furthermore, propyl acetate reduces the energy required for drying, thus easily mitigating environmental impact. Additionally, propyl acetate shortens drying time, thereby accelerating production speed.
[0138] Propyl acetate readily exhibits good compatibility with the substrate, thus facilitating the formation of a permeation layer on the substrate. Therefore, propyl acetate is preferred as a solvent from the perspective of ensuring good adhesion between the substrate and the functional layer. Propyl acetate exhibits particularly good compatibility with triacetyl cellulose and acrylic films, which have low heat resistance. Furthermore, propyl acetate readily controls the thickness of the permeation layer within the aforementioned range, thereby suppressing the reduction in the scratch resistance of the optical laminate and facilitating good adhesion. Solvents other than propyl acetate, such as dimethyl carbonate and other carbonates, are also excellent solvents with good compatibility with the substrate. However, solvents other than propyl acetate that are excellent with the substrate are difficult to control the thickness of the permeation layer within the aforementioned range. For example, dimethyl carbonate, which has excessively good compatibility with the substrate, can result in an excessively thick permeation layer, thereby reducing the scratch resistance of the optical laminate or deteriorating its appearance.
[0139] Toluene, which is widely used as a solvent, did not show the effects of the aforementioned propyl acetate due to its poor compatibility with substrates.
[0140] Furthermore, alkyl acetate esters other than propyl acetate, such as methyl acetate, ethyl acetate, and butyl acetate, have structures similar to propyl acetate, but they do not exhibit the effects described above. It is believed that the effects of propyl acetate arise from its inherent properties, such as solubility parameters and boiling points. These effects can be obtained using either n-propyl acetate or isopropyl acetate.
[0141] The ratio of propyl acetate to the total amount of solvent in the functional layer coating liquid is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0142] As described above, alkyl acetate esters other than propyl acetate, such as methyl acetate, ethyl acetate, and butyl acetate, did not exhibit the effects described above with propyl acetate. Furthermore, alkyl acetate esters other than propyl acetate tend to inhibit the effects of propyl acetate.
[0143] Therefore, the proportion of alkyl acetate other than propyl acetate to the total amount of solvent in the functional layer coating solution is preferably 9% by mass or less, more preferably 6% by mass or less.
[0144] Alkyl lactate esters, such as methyl lactate and ethyl lactate, have high miscibility with water. Therefore, if the functional layer coating solution contains alkyl lactate esters, moisture from the air can easily enter the functional layer during the production process. If moisture from the air enters the functional layer, it can sometimes lead to reduced particle dispersibility or decreased properties of the functional layer. Furthermore, alkyl lactate esters have a slow evaporation rate, making it difficult to obtain the desired optical properties when the drying temperature is lowered. Thus, alkyl lactate esters tend to hinder the effects of propyl acetate mentioned above.
[0145] Therefore, the ratio of alkyl lactate to the total amount of solvent in the functional layer coating liquid is preferably 9% by mass or less, and more preferably 6% by mass or less.
[0146] The mass ratio of solvent to the total amount of functional layer coating liquid is preferably 20% by mass or more and 90% by mass or less, more preferably 40% by mass or more and 80% by mass or less, and even more preferably 50% by mass or more and 70% by mass or less.
[0147] By using a solvent ratio of 20% by mass or more, good adhesion between the substrate and the functional layer can be easily achieved. Furthermore, by using a solvent ratio of 20% by mass or more, the functional layer coating liquid can be easily applied to the substrate, thus easily achieving good physical properties of the functional layer, such as scratch resistance.
[0148] By keeping the solvent ratio below 90% by mass, the concentration of propyl acetate in the optical laminate can be easily achieved to 15.00 mg / m³. 2 Furthermore, by keeping the solvent content at 90% by mass or less, the amount of solvent emitted into the external atmosphere during the manufacturing process of the optical laminate can be reduced, thus easily mitigating the environmental impact. Moreover, by keeping the solvent content at 90% by mass or less, the energy required to dry the functional layer coating solution can be reduced, thereby easily mitigating the environmental impact.
[0149] Toluene is not easily volatile and therefore remains in functional layers for extended periods. Consequently, the presence of toluene can easily contribute to sick building syndrome, leading to a deterioration of the living environment.
[0150] Therefore, the ratio of toluene to the total amount of solvent in the functional layer coating liquid is preferably 10% by mass or less, more preferably 5.5% by mass or less, and even more preferably 5% by mass or less.
[0151] In addition to toluene, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone can also remain in the functional layer for a long time, thus easily becoming a cause of sick building syndrome. Therefore, the total amount of toluene, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone relative to the total amount of solvent in the functional layer coating liquid is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less.
[0152] When forming the functional layer from the functional layer coating liquid, it is preferable to control drying conditions such as drying temperature, air velocity in the dryer, and drying time. At low drying temperatures, the concentration of solvents such as propyl acetate in the optical laminate tends to increase. At high drying temperatures, the physical properties of the functional layer may sometimes decrease. At slow drying air velocities, the concentration of solvents such as propyl acetate in the optical laminate tends to increase. At fast drying air velocities, the physical properties of the functional layer may sometimes decrease. If the drying time is short, the concentration of solvents such as propyl acetate in the optical laminate tends to increase. If the drying temperature is long, the physical properties of the functional layer may sometimes decrease. Furthermore, if the relative humidity is high, the concentration of solvents such as propyl acetate in the optical laminate tends to increase.
[0153] Therefore, the drying temperature is preferably 30°C or higher and 120°C or lower, more preferably 50°C or higher and 80°C or lower. The drying air velocity is preferably 0.2 m / s or higher and 50 m / s or lower, more preferably 2 m / s or higher and 40 m / s or lower. The drying time is preferably 5 seconds or higher and 180 seconds or lower, more preferably 15 seconds or higher and 100 seconds or lower. The relative humidity when forming the functional layer is preferably 70% or lower, more preferably 55% or lower.
[0154] For the optical laminate of this disclosure, the concentration of propyl acetate in the optical laminate, obtained by quantitative analysis using gas chromatography, needs to be 0.02 mg / m³. 2 Above and 15.00 mg / m 2 the following.
[0155] A tendency exists where a higher concentration of propyl acetate in the optical laminate results in a thicker permeation layer formed on the functional layer side of the substrate. Therefore, by setting the concentration of propyl acetate in the optical laminate to 0.02 mg / m³... 2 The above facilitates good adhesion between the substrate and the functional layer. Propylene acetate has good compatibility with the substrate, thus ensuring good adhesion not only initially but also over time. Furthermore, the good adhesion over time helps to suppress the decline in scratch resistance over time.
[0156] There is a tendency that the lower the concentration of propyl acetate in the optical laminate, the thinner the permeation layer formed on the functional layer side of the substrate, thus reducing the tendency for substrate components to flow into the functional layer. Furthermore, the lower the concentration of propyl acetate in the optical laminate, the easier it is for the resin in the functional layer to cure. Therefore, by setting the concentration of propyl acetate in the optical laminate to 15.00 mg / m³... 2 The following methods can easily suppress the decrease in scratch resistance of optical laminates. Furthermore, by setting the concentration of propyl acetate in the optical laminate to 15.00 mg / m³... 2 The following methods can easily reduce the environmental impact.
[0157] The concentration of propyl acetate in the optical laminate is preferably 0.05 mg / m³. 2 Above and 10.00 mg / m 2 The following is more preferably 0.10 mg / m³ 2 Above and 5.00 mg / m 2 the following.
[0158] As described above, alkyl acetate esters other than propyl acetate, such as methyl acetate, ethyl acetate, and butyl acetate, did not exhibit the effects described above with propyl acetate. Furthermore, alkyl acetate esters other than propyl acetate tend to inhibit the effects of propyl acetate.
[0159] Therefore, the optical laminate of this disclosure preferably has a concentration of alkyl acetate other than propyl acetate in the optical laminate, as determined by quantitative analysis using gas chromatography, of 0.35 mg / m³. 2 The following concentration is preferred: 0.30 mg / m³. 2 The following is a further preferred value: 0.20 mg / m³ 2 The following is a further preferred value: 0.15 mg / m² 2 the following.
[0160] Alkyl lactate esters, such as methyl lactate and ethyl lactate, have high miscibility with water. Therefore, if the functional layer coating solution contains alkyl lactate esters, moisture from the air can easily enter the functional layer during the production process. If moisture from the air enters the functional layer, it can sometimes lead to reduced particle dispersibility or decreased properties of the functional layer. Furthermore, alkyl lactate esters have a slow evaporation rate, making it difficult to obtain the desired optical properties when the drying temperature is lowered. Thus, alkyl lactate esters tend to hinder the effects of propyl acetate mentioned above.
[0161] Therefore, for the optical laminate of this disclosure, it is preferable that the concentration of alkyl lactate in the optical laminate, obtained by quantitative analysis using gas chromatography, is 0.45 mg / m³. 2 The above concentration is more preferably 0.40 mg / m³. 2 The following is a further preferred value: 0.30 mg / m³ 2 The following is a further preferred value: 0.15 mg / m² 2 the following.
[0162] For the optical laminate of this disclosure, it is preferable that the concentration of toluene in the optical laminate, obtained by quantitative analysis using gas chromatography, is 0.20 mg / m³. 2 The concentration of toluene is more preferably 0.17 mg / m³. 2 The following is a further preferred value: 0.15 mg / m³ 2 the following.
[0163] Toluene is not highly volatile and therefore remains in the functional layer for a long time. Therefore, by maintaining a toluene concentration of 0.20 mg / m³... 2 The following methods can easily suppress morbid building syndrome.
[0164] Toluene readily disperses particles, thus minimizing the formation of foreign matter or whitening caused by particle aggregation. Therefore, when the functional layer contains particles, the concentration of toluene in the optical laminate obtained by quantitative analysis using gas chromatography is preferably 0.01 mg / m³. 2 Above and 0.20 mg / m 2 The following is more preferably 0.05 mg / m³ 2 Above and 0.20 mg / m 2 the following.
[0165] For the optical laminate of this disclosure, it is preferred that the total concentration of toluene, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone in the optical laminate, obtained by quantitative analysis using gas chromatography, is 1.00 mg / m³. 2 The following is a preferred total concentration: 0.80 mg / m³. 2 The following is a further preferred value: 0.50 mg / m³ 2 the following.
[0166] Toluene, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone are not easily volatile and therefore remain in the functional layer for a long time. Therefore, by maintaining the total concentration at 1.00 mg / m³... 2 The following methods can easily suppress morbid building syndrome.
[0167] In this specification, the concentration of solvents such as propyl acetate contained in the optical laminate is determined according to steps (1) and (2) below. Furthermore, regarding the concentration of solvents in the optical laminate, the sample collected from the optical laminate is sealed in a sample vial, and this is performed using a sealed sample vial. Sealing the sample in the sample vial is preferably performed within one hour after the optical laminate is completed by forming all functional layers on the substrate.
[0168] (1) Perform qualitative analysis of the solvent contained in the optical laminate.
[0169] (2) Quantitative analysis was performed on the solvents detected in the qualitative analysis in (1) above. The quantitative analysis was performed using the absolute calibration curve method.
[0170] It should be noted that the concentration of the solvent in the optical laminate does not change significantly after the optical laminate is manufactured. Therefore, samples collected from commercially available optical laminates can be sealed in vials, and the solvent concentration can be determined using the sealed vials. Examples of commercially available optical laminates include those assembled into panels or image display devices.
[0171] <Other Features>
[0172] The total light transmittance of the optical laminate according to JIS K7361-1:1997 is preferably 70% or more, more preferably 80% or more, and even more preferably 85% or more.
[0173] When an anti-glare layer is included as a functional layer, for the optical laminate, the haze according to JIS K7136:2000 is preferably 1% or more and 75% or less. The lower limit of haze is more preferably 1% or more, further preferably 10% or more, even more preferably 15% or more, and the upper limit is more preferably 70% or less, and even more preferably 65% or less.
[0174] When an anti-glare layer is included as a functional layer, the upper limit of the 60-degree specular gloss measured from the anti-glare layer side is preferably 100 or less, more preferably 55 or less, and even more preferably 40 or less; the lower limit is preferably 5 or more, more preferably 10 or more, and even more preferably 15 or more. In this specification, 60-degree specular gloss refers to the 60-degree specular gloss measured by method 3 specified in JIS Z8741:1997.
[0175] Unless otherwise specified, in this instruction manual, haze, total transmittance and 60-degree specular gloss refer to the average of 14 measurements taken from 16 locations after removing the maximum and minimum values.
[0176] In this specification, regarding the 16 measurement sites, a region 1 cm from the outer edge of the sample is removed as a blank. For the remaining region, the 16 intersection points of lines drawn into five equal parts in both the longitudinal and transverse directions are used as the measurement centers. For example, when the sample is rectangular, a region 0.5 cm from the outer edge of the rectangle is removed as a blank, and the remaining region is measured at the 16 intersection points of the five equal parts in both the longitudinal and transverse directions. Furthermore, the average of the 14 measurement values after removing the maximum and minimum values from the 16 measurements is used as the parameter value. When the sample is a shape other than a rectangle, such as a circle, ellipse, triangle, or pentagon, a rectangle inscribed in these shapes is drawn, and for these rectangles, 16 measurements are performed using the method described above.
[0177] <Size, shape, etc.>
[0178] Optical laminates can be in the form of single-leaf shapes cut to a specified size, or in the form of rolls formed by rolling long sheets into a roll. There is no particular limitation on the size of a single leaf, with a maximum diameter of approximately 2 inches to 500 inches. "Maximum diameter" refers to the maximum length connecting any two points of the optical laminate. For example, in the case of a rectangular optical laminate, the diagonal of that region is the maximum diameter. In the case of a circular optical laminate, the diameter of the circle is the maximum diameter.
[0179] There are no particular limitations on the width and length of the roll; typically, the width is between 500mm and 3000mm, and the length is between 500m and 5000m. Roll-shaped optical laminates can be cut into single-leaf shapes according to the size of image display devices, etc., except for the unstable ends of the roll during cutting.
[0180] The shape of a single leaf is not particularly limited; for example, it can be a polygon such as a triangle, quadrilateral, or pentagon, a circle, or a random, amorphous shape. More specifically, when the optical laminate is quadrilateral, the aspect ratio is not particularly limited as long as it does not pose a problem for the display image. For example, aspect ratios such as 1:1, 4:3, 16:10, 16:9, and 2:1 can be used, but in highly designed automotive applications or digital signage, these aspect ratios are not limited.
[0181] As long as the concentration of propyl acetate in the optical laminate is 15.00 mg / m³ 2 The following ensures sufficient scratch resistance when conveying roll-shaped and leaf-shaped optical laminates.
[0182] [Polarizing filter]
[0183] The polarizer disclosed herein is a polarizer having a polarizing element, a first transparent protective plate disposed on one side of the polarizing element, and a second transparent protective plate disposed on the other side of the polarizing element, wherein, At least one of the first transparent protective plate and the second transparent protective plate is the optical laminate described above.
[0184] <Polarization element>
[0185] Examples of polarizing elements include sheet-type polarizing elements such as polyvinyl alcohol films dyed and stretched with iodine, polyvinyl alcohol formal films, polyvinyl alcohol acetal films, and ethylene-vinyl acetate copolymer saponified films; wire grid-type polarizing elements composed of a large number of parallel metal lines; coated polarizing elements coated with lyotropic liquid crystals or dichroic host-guest materials; and multilayer thin film polarizing elements. These polarizing elements can also be reflective polarizing elements that have the function of reflecting polarizing components while not transmitting them.
[0186] <Transparent Protective Panel>
[0187] A first transparent protective plate is disposed on one side of the polarizing element, and a second transparent protective plate is disposed on the other side. At least one of the first and second transparent protective plates is the optical laminate described above.
[0188] For the polarizer of this disclosure, one of the first transparent protective plate and the second transparent protective plate may be the optical laminate of this disclosure as described above, or both the first transparent protective plate and the second transparent protective plate may be the optical laminate of this disclosure as described above.
[0189] In the first and second transparent protective plates, the transparent protective plates, which are not optical laminates disclosed herein, can be made of common plastic film and glass, etc.
[0190] The polarizing element and the transparent protective plate are preferably bonded together using an adhesive. A general-purpose adhesive can be used, but a PVA-based adhesive is preferred.
[0191] [Surface plate for image display device]
[0192] The surface plate for the image display device disclosed herein is a surface plate for an image display device having a protective film laminated on a resin plate or glass plate, wherein the protective film is the optical laminate of the present disclosure described above.
[0193] As a resin plate or glass plate, a resin plate or glass plate that is commonly used as a surface plate for image display devices can be used.
[0194] To ensure good strength, the thickness of the resin or glass sheet is preferably 10 μm or more. The upper limit of the thickness of the resin or glass sheet is typically 5000 μm or less. For thinner profiles, the upper limit of the thickness of the resin or glass sheet is preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 100 μm or less.
[0195] Examples of embodiments for the thickness range of the resin plate or glass plate include 10 μm or more and 5000 μm or less, 10 μm or more and 1000 μm or less, 10 μm or more and 500 μm or less, and 10 μm or more and 100 μm or less.
[0196] [panel]
[0197] The panel disclosed herein is a panel having a display element and an optical laminate disposed on the light emitting surface side of the display element, wherein the optical laminate comprises the optical laminate of the present disclosure described above (see reference). Figure 2 ).
[0198] Examples of display elements include liquid crystal displays, EL displays (organic EL displays, inorganic EL displays), plasma displays, and LED displays such as micro LED displays. These display elements may also have touch panel functionality within their internal components.
[0199] The display methods of liquid crystals as liquid crystal display elements can include IPS, VA, multi-domain, OCB, STN, TSTN, etc.
[0200] In addition, the panel disclosed herein may be a panel with a touch panel having a touch panel between the display element and the optical laminate.
[0201] There is no particular limit to the size of the panel, but the maximum diameter is approximately 2 inches to 500 inches. The maximum diameter refers to the maximum length that can be connected to any two points within the panel.
[0202] [Image display device]
[0203] The image display device disclosed herein includes the panel of this disclosure. The concentration of propyl acetate in the optical laminate assembled in the image display device is 15.00 mg / m³. 2 The following ensures sufficient scratch resistance during the transport and use of the image display device.
[0204] The image display device disclosed herein is not particularly limited as long as it includes the panel of this disclosure. Preferably, the image display device of this disclosure includes the panel of this disclosure, a drive control unit electrically connected to the panel, and a frame housing them.
[0205] When the display element is a liquid crystal display element, the image display device of this disclosure requires a backlight. The backlight is disposed on the side of the liquid crystal display element opposite to the light emitting surface side.
[0206] There is no particular limitation on the size of the image display device, but the maximum diameter of the effective display area is approximately 2 inches or more and less than 500 inches.
[0207] The effective display area of an image display device is the area capable of displaying an image. For example, in the case where the image display device has a housing surrounding the display element, the area inside the housing becomes the effective image area.
[0208] Furthermore, the maximum diameter of the effective image region refers to the maximum length that connects any two points within the effective image region. For example, if the effective image region is rectangular, its diagonal is the maximum diameter. Conversely, if the effective image region is circular, its diameter is the maximum diameter.
[0209] [Manufacturing method of optical laminates]
[0210] The method for manufacturing the optical laminate disclosed herein is as follows.
[0211] A method for manufacturing an optical laminate includes a step of coating a functional layer coating liquid onto a substrate and a step of drying the functional layer coating liquid. The functional layer coating solution contains propyl acetate as a solvent. The concentration of propyl acetate in the optical laminate is 0.02 mg / m³, as determined by quantitative analysis using gas chromatography. 2 Above and 15.00 mg / m 2 The following methods are used for manufacturing.
[0212] The substrate, composition of the functional layer coating liquid, coating method of the functional layer coating liquid, and drying conditions of the functional layer coating liquid in the manufacturing method of the optical laminate disclosed herein can be the same as the embodiments exemplified in the optical laminate of the present disclosure described above.
[0213] For example, in the method for manufacturing the optical laminate disclosed herein, the concentration of alkyl acetates other than propyl acetate in the optical laminate is preferably 0.35 mg / m³. 2 The following methods are used for manufacturing.
[0214] Furthermore, the method for manufacturing the optical laminate disclosed herein preferably uses an alkyl lactate concentration of 0.45 mg / m³ in the optical laminate. 2 The following methods are used for manufacturing.
[0215] Furthermore, in the method for manufacturing the optical laminate disclosed herein, the concentration of toluene in the optical laminate is preferably 0.20 mg / m³. 2 The following methods are used for manufacturing.
[0216] According to the method for manufacturing optical laminates disclosed herein, it is possible to efficiently manufacture optical laminates that can suppress the degradation of adhesion and scratch resistance over time.
[0217] [Selection Methods for Optical Laminates]
[0218] The method for selecting optical laminates disclosed herein selects optical laminates that satisfy the following selection criteria.
[0219] (Selection criteria for optical laminates)
[0220] An optical laminate having at least one functional layer on a substrate, wherein the concentration of propyl acetate in the optical laminate, as determined by gas chromatography, is 0.02 mg / m³. 2Above and 15.00 mg / m 2 the following.
[0221] In the optical laminate selection method disclosed herein, one or more additional selection conditions may be included. Preferred embodiments of the optical laminate can be cited as examples of these additional selection conditions. Examples of these additional selection conditions include A through F described below.
[0222] A: The concentration of toluene in the optical laminate is 0.20 mg / m³. 2 the following.
[0223] B: The substrate has a permeation layer on one side of the side having the functional layer, and the thickness of the permeation layer is more than 0.20 μm and less than 1.50 μm.
[0224] C: The functional layer contains particles.
[0225] D: The total transmittance of the optical laminate is above 80%.
[0226] E: The concentration of alkyl acetates other than propyl acetate in the optical laminate is 0.35 mg / m³. 2 the following.
[0227] F: The concentration of alkyl lactate in the optical laminate is 0.45 mg / m³. 2 the following.
[0228] According to the optical laminate selection method disclosed herein, it is possible to efficiently select optical laminates that can suppress the degradation of adhesion and scratch resistance over time.
[0229] This disclosure includes the following <1> ~ <16> .
[0230] <1> An optical laminate having at least one functional layer on a substrate, wherein the concentration of propyl acetate in the optical laminate, as determined by gas chromatography, is 0.02 mg / m³. 2 Above and 15.00 mg / m 2 the following.
[0231] <2> according to <1> The optical laminate, wherein the propyl acetate comprises at least one of n-propyl acetate and isopropyl acetate.
[0232] <3> according to <1> or <2> The optical laminate, wherein the concentration of toluene in the optical laminate, as determined by quantitative analysis using gas chromatography, is 0.20 mg / m³. 2 the following.
[0233] <4> according to <1> ~ <3> In any one of the optical laminates, the substrate has a permeable layer on the side having the functional layer, the thickness of the permeable layer being 0.20 μm or more and 1.50 μm or less.
[0234] <5> according to <1> ~ <4> The optical laminate according to any one of the following, wherein the functional layer comprises particles.
[0235] <6> according to <5> The optical laminate, wherein the particles comprise one or more particles selected from organic particles and inorganic particles.
[0236] <7> according to <5> The optical laminate, wherein the concentration of toluene in the optical laminate, as determined by quantitative analysis using gas chromatography, is 0.05 mg / m³. 2 Above and 0.20 mg / m 2 the following.
[0237] <8> according to <1> ~ <7> In any one of the optical laminates, the concentration of alkyl acetates other than propyl acetate in the optical laminate, as determined by quantitative analysis using gas chromatography, is 0.35 mg / m³. 2 the following.
[0238] <9> according to <1> ~ <8> In any one of the optical laminates, the concentration of alkyl lactate in the optical laminate, as determined by gas chromatography quantitative analysis, is 0.45 mg / m³. 2 the following.
[0239] <10> according to <1> ~ <9> The optical laminate described in any one of the following methods includes an anti-glare layer as the functional layer.
[0240] <11> A polarizer comprising a polarizing element, a first transparent protective plate disposed on one side of the polarizing element, and a second transparent protective plate disposed on the other side of the polarizing element, wherein... At least one of the first transparent protective plate and the second transparent protective plate is <1> ~ <10> The optical laminate as described in any one of the following.
[0241] <12> A surface panel for an image display device, comprising a protective film laminated onto a resin plate or glass plate, wherein the protective film is... <1> ~ <10> The optical laminate as described in any one of the following.
[0242] <13> A panel having a display element and an optical laminate disposed on the light emitting surface side of the display element, wherein the panel includes... <1> ~ <10> The optical laminate described in any one of the above statements is the optical laminate.
[0243] <14> An image display device comprising <13> The aforementioned panel.
[0244] <15> A method for manufacturing an optical laminate includes a step of coating a functional layer coating liquid onto a substrate and a step of drying the functional layer coating liquid. The functional layer coating solution contains propyl acetate as a solvent, and the concentration of propyl acetate in the optical laminate, obtained by quantitative analysis using gas chromatography, is 0.02 mg / m³. 2 Above and 15.00 mg / m 2 The following methods are used for manufacturing.
[0245] <16> A method for selecting an optical laminate, wherein the optical laminate satisfies the following selection criteria. Selection criteria for optical laminates: An optical laminate, comprising at least one functional layer on a substrate, wherein the concentration of propyl acetate in the optical laminate, as determined by gas chromatography, is 0.02 mg / m³. 2 Above and 15.00 mg / m 2 the following.
[0246] Example
[0247] The present disclosure will now be described in more detail by way of examples, but the disclosure is not limited to these examples in any way. Unless otherwise stated, “parts” and “%” are based on mass.
[0248] 1. Measurement and evaluation
[0249] The optical laminates of the Examples, Comparative Examples, and Reference Examples were measured and evaluated as follows. Unless otherwise specified, the atmosphere used for each measurement and evaluation was set at a temperature of 23°C ± 1°C and a relative humidity of 40% to 65%. In addition, except for the qualitative analysis in 1-1(1) and the quantitative analysis in 1-1(2), the sample was exposed to the atmosphere for 30 minutes before each measurement and evaluation. The results are shown in Table 1 or 2.
[0250] 1-1. Solvent concentration
[0251] Qualitative analysis of solvents such as propyl acetate contained in the optical laminates of the Examples, Comparative Examples, and Reference Examples was performed. Then, quantitative analysis was performed on the detected solvents. The qualitative and quantitative analyses were performed according to the following steps. The quantitative analysis was completed within one hour after the functional layer was formed on the substrate.
[0252] (1) Qualitative Analysis
[0253] Cut a 5cm × 5cm sample for qualitative analysis from the optical laminate and seal it in the sample vial provided with the apparatus. Complete the sealing process within one hour of completing the optical laminate. Place the sample vial in the heating desorption apparatus described below. Using the apparatus that connects the heating desorption apparatus described below to the gas chromatograph-mass spectrometer described below, perform qualitative analysis of the sample under the following conditions. Extract substances with a melting point above 25°C and a boiling point below 200°C from the obtained peaks as residual solvents.
[0254] <Heating and Desorption Device (Pretreatment Device)>
[0255] Device Name: JTD505 III (Analysis Industries, Inc., Japan)
[0256] "condition"
[0257] Sample tube heating temperature: 100℃
[0258] Cold trap cooling temperature: -60℃
[0259] Cold trap heating temperature: 315℃
[0260] Purging time: 20 minutes
[0261] Overall split ratio (inlet volume: exhaust volume) = 1:10
[0262] Column flow rate: 2 ml / min
[0263] Gas Chromatography-Mass Spectrometry
[0264] Device Name: Agilent 6890 / 5973 (Agilent Technologies)
[0265] "condition"
[0266] Column temperature: 50℃ for 5 minutes (hold), 10℃ / minute (increase), 320℃ for 3 minutes (hold)
[0267] Pillar Information
[0268] Product Number: UA-5 (Frontier Laboratories)
[0269] Stationary phase: 5% phenyl, 95% dimethylsiloxane
[0270] Polarity: Micropolarity
[0271] Inner diameter: 0.25mm
[0272] Length: 30m
[0273] Film thickness: 0.25μm
[0274] (2) Quantitative analysis
[0275] Cut a 10cm × 10cm sample for quantitative analysis from the optical laminate and seal it in the sample vial provided with the apparatus. Complete the sealing within one hour after the optical laminate is completed. Place the sample vial in the apparatus described below. For the solvents detected in the qualitative analysis above (1), perform quantitative analysis of the sample using the apparatus described below under the following conditions. The concentrations of each solvent are shown in Table 2. The quantitative analysis described below is performed using the absolute calibration curve method.
[0276] <device>
[0277] Device Name: HP-5973N (Agilent Technologies)
[0278] <Conditions>
[0279] Heating temperature: 120℃
[0280] Heating time: 30 minutes
[0281] Inlet temperature: 250℃
[0282] Sample injection volume: 1 mL
[0283] Column temperature: 50℃ for 5 minutes (hold), 10℃ / minute (increase), 200℃ (no hold)
[0284] Split ratio = 20:1 (column flow rate 1.0 ml / min, linear velocity 21 cm / s)
[0285] Detector: Flame Ionization Detector (FID)
[0286] Pillar Information
[0287] Product Name: GL Sciences "InertCap5MS / Sil"
[0288] Polarity: Micropolarity
[0289] Stationary phase: 100% dimethylsiloxane
[0290] Film thickness: 0.25μm
[0291] Inner diameter: 0.25mm
[0292] Length: 30m
[0293] 1-2. Fit
[0294] (1) Initial tightness
[0295] The adhesion of the optical laminates of the embodiments, comparative examples and reference examples was evaluated using the following methods.
[0296] The evaluation samples were cross-cut into a checkerboard pattern of 100 squares (10 vertical and 10 horizontal). The cutting interval was 1 mm. During cutting, the cutter blade entered from the functional layer side, and the cross-cut was performed so that the cutter blade reached the top of the substrate.
[0297] Adhesive tape (manufactured by NICHIBAN Co., Ltd., product name "Cellotape" (registered trademark)) was applied to the surface of the cross-cut samples, and a peel test was performed according to the cross-cut method specified in JIS K 5600-5-6:1999. The number of cells remaining after the peel test out of 100 cells was determined. The closer the number of remaining cells is to 100, the better the adhesion.
[0298] (2) Adhesion after durability test
[0299] After performing the following durability tests on the optical laminates of the examples, comparative examples and reference examples, the fit was evaluated in the same manner as in (1) above.
[0300] <Durability Testing>
[0301] The lightfastness and weather resistance tester based on JIS B7751:2007 (trade name "FAL-AU·B" manufactured by Suga Testing Machine Co., Ltd.), using an ultraviolet carbon arc lamp as the light source and an irradiance of 500 W / m², was used. 2 Within the range of 63°C (black panel temperature), the optical laminates of the embodiments, comparative examples, and reference examples were arranged with the functional layer side facing the light source, and a 200-hour test was conducted.
[0302] 1-3. Scratch resistance after durability testing
[0303] The above-described durability test was performed on the optical laminates of the embodiments, comparative examples, and reference examples.
[0304] After durability testing, the optical laminate was cut into 3cm × 20cm samples. After visually confirming the absence of dust, scratches, or other abnormalities, cut points were randomly selected. Next, a steel wool testing machine (SAM JEE TECK, trade name "SJTR-053") was used to apply a load of 1000g / cm² to the functional layer side of the optical laminate sample. 2 Press the steel wool #0000 (product name: BONSTAR, Japan Steel Wool Co., Ltd.) and rub it back and forth 10 times at a speed of 100 mm / s. The length of the triboelectric laminate is 17 cm in a single pass. The contact area between the steel wool and the sample is 4 cm². 2Then, black adhesive tape is applied to the side of the substrate opposite to the side with the functional layer. Then, under illumination by a 3-wavelength fluorescent lamp, the functional layer of the optical laminate sample is visually inspected for scratches and discoloration, and evaluated according to the following criteria. Discoloration is a phenomenon caused by the removal or deformation of the raised portion of the anti-glare layer.
[0305] AA: No scratches or discoloration
[0306] A: No scratches, but discoloration.
[0307] B: Discoloration occurs, and the number of scratches is more than 1 and less than 10.
[0308] C: Discoloration occurs, and the number of scratches is between 11 and 20.
[0309] D: Discoloration occurs, and the number of scratches is 21 or more.
[0310] 1-4. Thickness
[0311] The thickness of the permeation layer was measured using STEM (Scanning Transmission Electron Microscopy) on a sample exposed in the cross-section of an optical laminate. The sample was prepared according to procedures (A1) to (A2) in the main text of the instruction manual. The silicon embedding plate for (A1) was a silicon embedding plate manufactured by Dosaka EM Co., Ltd. The epoxy resin used for embedding in (A1) was a resin prepared by mixing Struers' trade name "Epofix" and its trade name "Epofix Curing Agent" at a ratio of 10:1.2. The resin for embedding in (A1) was cured by leaving it at room temperature for 12 hours. The apparatus for cutting the block-shaped embedded sample in (A2) was a Leica Microsystems trade name "UltraMicrotome EM UC7". When cutting the block-shaped embedded sample, an initial rough cut (coarse trimming) was performed, followed by precise trimming under conditions of "SPEED: 1.00 mm / s" and "FEED: 70 nm". The samples used for the assay were stained with osmium tetroxide.
[0312] STEM uses Hitachi High Technology Corporation's product number "S-4800". The camera conditions are as follows.
[0313] <Filming Conditions>
[0314] Mode: TE
[0315] Accelerating voltage: 30kV
[0316] Transmitting current: 10uA
[0317] WD (Working Distance): 8.0mm
[0318] Magnification: 100,000x based on High magnification mode
[0319] 1-5. Total transmittance and haze (Hz)
[0320] The optical laminates of the examples, comparative examples, and reference examples were cut into 10cm square pieces. After visually confirming the absence of dust, scratches, or other abnormalities, cut sections were randomly selected. Using a haze meter (HM-150, Murakami Color Technology Research Institute), the total transmittance according to JIS K7361-1:1997 and the haze according to JIS K7136:2000 were measured for each sample.
[0321] To stabilize the light source, turn on the power switch of the device and wait for more than 15 minutes beforehand. Perform calibration with nothing set at the entrance opening, and then set the sample at the entrance opening for measurement. The light incident surface is the substrate side.
[0322] 1-6.60 degrees of specular gloss
[0323] A 10cm × 5cm sample was cut from the optical laminates of the examples, comparative examples, and reference examples. The samples were visually confirmed to be free of dust, scratches, or other abnormalities. After the matte black resin plate was brought into close contact with the substrate side of the sample using an air suction method, the specular gloss at 60 degrees was measured from the functional layer side of the sample. The specular gloss was measured using a gloss meter “GM-26PRO” manufactured by Murakami Color Technology Research Institute. The black resin plate was an accessory to the gloss meter.
[0324] 1-7. Appearance Quality
[0325] Samples were prepared by bonding a black plate (Kuraray, COMOGLASS DFA2CG 502K (Black) series, 0% total transmittance, 2mm thickness, refractive index 1.49) to the substrate side of the optical laminates of the Examples, Comparative Examples, and Reference Examples. The samples were 20cm long x 30cm wide. The samples were placed on a horizontal platform in a brightly lit room (illuminance of 500–1000 lux on the optical laminates; illumination: Hf32 type straight tube 3-wavelength daylight fluorescent lamp, positioned 2m above the horizontal platform vertically). Twenty subjects evaluated the samples. Evaluation criteria included "whether anti-glare was achieved to a degree where the observer's own reflection was not noticeable" and "whether whitening was noticeable," and were graded according to the following criteria.
[0326] A: More than 14 people answered that the anti-glare performance is good and they don't mind the whitening effect.
[0327] B: 7 to 13 people answered that the anti-glare performance is good and they don't mind the whitening effect.
[0328] C: Fewer than 6 people answered that the anti-glare performance was good and they didn't mind the whitening effect.
[0329] 2. Fabrication of optical laminates
[0330] [Example 1]
[0331] The functional layer coating solution described below was applied to a substrate (40 μm thick triacetyl cellulose resin film, Fujifilm). Then, it was dried at 80°C and an air velocity of 10 m / s for 60 seconds. Next, it was dried under a nitrogen atmosphere with an oxygen concentration of less than 200 ppm until the cumulative light intensity reached 150 mJ / cm². 2 By irradiating ultraviolet light in a certain way, an anti-glare layer with a thickness of 4.8 μm is formed as a functional layer, resulting in the optical laminate of Example 1.
[0332] <Functional Layer Coating Liquid>
[0333] · 100 parts of adhesive
[0334] (Pentaerythritol triacrylate)
[0335] (Nippon Kayaku Co., Ltd., Trade Name: KAYARAD-PET-30)
[0336] · 1.0 part organic granules
[0337] (Spherical polyacrylic acid-styrene copolymer from Sekisui Chemicals Co., Ltd., average particle size 3.0 μm, refractive index 1.550)
[0338] 14 parts of inorganic silica particles
[0339] (Average particle size: 4.1 μm) (Manufactured by Fuji Silysia Chemical Co., Ltd., gel-processed amorphous silica)
[0340] · 5 parts of photopolymerization initiator
[0341] (IGM Resins BV, product name: Omnirad 184)
[0342] · 0.2 parts silicone-based leveling agent
[0343] (Momentive Performance Materials, product name: TSF4460)
[0344] • Solvent (n-propyl acetate) 175 parts
[0345] • Solvent (MIBK) 10 parts
[0346] • Solvent (ethyl acetate) 5.2 parts
[0347] [Examples 2-10], [Comparative Examples 1-4], [Reference Examples 1-2]
[0348] The types and amounts of solvents contained in the functional layer coating solution were changed to those in Table 1. Additionally, the drying conditions were changed to those in Table 1. Apart from these changes, optical laminates of Examples 2-10, Comparative Examples 1-4, and Reference Examples 1-2 were obtained in the same manner as in Example 1.
[0349] [Table 1]
[0350] [Table 2]
[0351] The results in Table 2 confirm that the optical laminates of the examples exhibit good adhesion and scratch resistance after durability testing, and can suppress the degradation of adhesion and scratch resistance over time. It should be noted that, according to Table 1, toluene was not added as a solvent to the functional layer coating solutions of Examples 1-10, Comparative Examples 2-4, and Reference Examples 1-2. However, toluene was detected in the optical laminates of Examples 1-10 and Comparative Examples 2-6 in Table 2. This is because toluene was detected as a residual solvent in the binder components and photopolymerization initiator.
[0352] It should be noted that the "thickness of the permeation layer" in Table 2 is the result measured using the above-mentioned embedded samples. Additionally, the items other than "thickness of the permeation layer" in Table 2 are the results measured using samples cut from the optical laminate.
[0353] Explanation of reference numerals in the attached figures
[0354] 10: Substrate
[0355] 20: Functional Layer
[0356] 21: Functional Layer 1
[0357] 22: Second functional layer
[0358] 100: Optical laminate
[0359] 200: Display element
[0360] 300: Panel
Claims
1. An optical laminate, wherein the optical laminate has at least one or more functional layers on a substrate, wherein, The concentration of propyl acetate in the optical laminate, as determined by gas chromatography, was 0.02 mg / m³. 2 Above and 15.00 mg / m 2 the following.
2. The optical laminate according to claim 1, wherein, The propyl acetate includes at least one of n-propyl acetate and isopropyl acetate.
3. The optical laminate according to claim 1, wherein, The concentration of toluene in the optical laminate, as determined by gas chromatography, was 0.20 mg / m³. 2 the following.
4. The optical laminate according to claim 1, wherein, The substrate has a permeable layer on one side of the side having the functional layer, and the thickness of the permeable layer is more than 0.20 μm and less than 1.50 μm.
5. The optical laminate according to claim 1, wherein, The functional layer contains particles.
6. The optical laminate according to claim 5, wherein, The particles include one or more particles selected from organic particles and inorganic particles.
7. The optical laminate according to claim 5, wherein, The concentration of toluene in the optical laminate, as determined by gas chromatography, was 0.05 mg / m³. 2 Above and 0.20 mg / m 2 the following.
8. The optical laminate according to claim 1, wherein, The concentration of alkyl acetates other than propyl acetate in the optical laminate, as determined by gas chromatography, was 0.35 mg / m³. 2 the following.
9. The optical laminate according to claim 1, wherein, The concentration of alkyl lactate in the optical laminate, as determined by gas chromatography, was 0.45 mg / m³. 2 the following.
10. The optical laminate according to claim 1, wherein an anti-glare layer is included as the functional layer.
11. A polarizer comprising a polarizing element, a first transparent protective plate disposed on one side of the polarizing element, and a second transparent protective plate disposed on the other side of the polarizing element, wherein, At least one of the first transparent protective plate and the second transparent protective plate is an optical laminate as described in any one of claims 1 to 10.
12. A surface panel for an image display device, wherein a protective film is laminated onto a resin plate or glass plate, wherein... The protective film is an optical laminate as described in any one of claims 1 to 10.
13. A panel having a display element and an optical laminate disposed on the light-emitting surface side of the display element, wherein, The optical laminate comprising any one of claims 1 to 10 is said optical laminate.
14. An image display device comprising the panel of claim 13.
15. A method for manufacturing an optical laminate, comprising the steps of coating a functional layer coating liquid onto a substrate and drying the functional layer coating liquid, wherein... The functional layer coating solution contains propyl acetate as a solvent, and the concentration of propyl acetate in the optical laminate, obtained by quantitative analysis using gas chromatography, is 0.02 mg / m³. 2 Above and 15.00 mg / m 2 The following methods are used for manufacturing.
16. A method for selecting an optical laminate, wherein the optical laminate that satisfies the following selection conditions is selected. Selection criteria for optical laminates: An optical laminate, comprising at least one functional layer on a substrate, wherein the concentration of propyl acetate in the optical laminate, as determined by gas chromatography, is 0.02 mg / m³. 2 Above and 15.00 mg / m 2 the following.
Citation Information
Patent Citations
Antiglare hard coat film, manufacturing method of antiglare hard coat film, optical member and image display apparatus
JP2021124616A
Anti-glare film, method for manufacturing anti-glare film, optical member, and image display device
JP2022183161A
Antiglare film laminate, polarizing plate, and display device
JP2023516178A
